Analysis Internal Factors Of Bank Performance On Bank’s Profitability in Indonesia - Liliani Reskita; Purwanto - (Management and Leadership Study Programme, 2019)
This research aims to analyze internal factor n bank performance was influenced by usingmacroeconomic factor as control variable. The determinants used for internal factor ofbank consist of size, liquidity, capital and credit risk with control variable such as GDPand inflation. Quantitative method is used and for the sample suddenly stand up from 15banks with specific criteria that include in Indonesia Stock Exchange. Based on themultiple regression conclude that concluded size, capital, credit risk and inflation havesignificant positive effect on Return on Asset, while liquidity and GDP have a significantnegative effect on Return on Asset.